CAM-ICU may not be the optimal screening tool for early delirium screening in older emergency department patients: a prospective cohort study. (December 2019) - Lucke, Jacinta A.; De Gelder, Jelle; Blomaard, Laura C.; Fogteloo, Anne J.; Alsma, Jelmer; Schuit, Stephanie C.E.; Brink, Anniek; De Groot, Bas; Blauw, Gerard J.; Mooijaart, Simon P.
Abstract : Objectives: Delirium is a frequent problem among older patients in the emergency department (ED) and early detection is important to prevent its associated adverse outcomes. Several screening tools for delirium have been proposed for the ED, such as the 6-Item Cognitive Impairment Test (6-CIT) and the Confusion Assessment Method-ICU (CAM-ICU). Previous validation of the CAM-ICU for use in the ED showed varying results, possibly because it was administered at different or unknown time points. The aim was to study the prevalence of delirium in older ( ≥ 70 years) ED patients using the CAM-ICU and 6-CIT. Participants and methods: A prospective cohort study was carried out in one tertiary care and one secondary care hospital in the Netherlands. Patients aged 70 years and older attending the ED were included. Delirium screening was performed within 1 h after ED registration using the CAM-ICU. The 6-CIT was determined for comparison using a cut-off point of at least 14 points indicating possible delirium. Results: A total of 997 patients were included in the study, with a median age of 78 years (interquartile range 74–84). Delirium as assessed with CAM-ICU was positive in only 13 (1.3%, 95% confidence interval: 0.8–2.2) patients. Ninety-five (9.5% 95% confidence interval: 7.9–11.5) patients had 6-CIT more than or equal to 14. Conclusion: We found a delirium prevalence of 1.3% using the CAM-ICU, which was much lower than the expected prevalence of around 10% as being frequently reported in the literature and what we found when using the 6-CIT. On the basis of these results, caution is warranted to use the CAM-ICU for early screening in the ED.